Flexible pH‐Sensing Hydrogel Fibers for Epidermal Applications. Issue 6 (22nd January 2016) - Tamayol, Ali; Akbari, Mohsen; Zilberman, Yael; Comotto, Mattia; Lesha, Emal; Serex, Ludovic; Bagherifard, Sara; Chen, Yu; Fu, Guoqing; Ameri, Shideh Kabiri; Ruan, Weitong; Miller, Eric L.; et al.
Abstract : Epidermal pH is an indication of the skin's physiological condition. For example, pH of wound can be correlated to angiogenesis, protease activity, bacterial infection, etc. Chronic nonhealing wounds are known to have an elevated alkaline environment, while healing process occurs more readily in an acidic environment. Thus, dermal patches capable of continuous pH measurement can be used as point‐of‐care systems for monitoring skin disorder and the wound healing process. Here, pH‐responsive hydrogel fibers are presented that can be used for long‐term monitoring of epidermal wound condition. pH‐responsive dyes are loaded into mesoporous microparticles and incorporated into hydrogel fibers using a microfluidic spinning system. The fabricated pH‐responsive microfibers are flexible and can create conformal contact with skin. The response of pH‐sensitive fibers with different compositions and thicknesses are characterized. The suggested technique is scalable and can be used to fabricate hydrogel‐based wound dressings with clinically relevant dimensions. Images of the pH‐sensing fibers during real‐time pH measurement can be captured with a smart phone camera for convenient readout on‐site. Through image processing, a quantitative pH map of the hydrogel fibers and the underlying tissue can be extracted. The developed skin dressing can act as a point‐of‐care device for monitoring the wound healing process. Abstract : pH‐responsive hydrogel fibers that can be used for long‐term monitoring of epidermal wound condition are generated. PH‐responsive dye is loaded into mesoporous microparticles, which are then embedded into hydrogel fibers developed through microfluidic spinning. The fabricated pH‐responsive microfibers are flexible and can create conformal contact with skin. Images of the pH‐sensing fibers during real‐time pH measurement can be captured with a smart phone camera for convenient readout on‐site.